Formulasi Nilai Tambah pada Rantai Pasok Minyak Sawit - Syarif Hidayat; Nunung Nurhasanah; Rizki Ayuning Prasongko (Jurnal Optimasi Sistem Industri, 2014)
In palm oil supply chain (POSC) the smallholder farmers sell their fresh fruit bunch (FFB) to Palm Oil Mills through traders. Palm Oil Mills convert the FFB into crude palm oil (CPO). CPO is sold to the refinery, who converts CPO into frying oil and sends the product to the distributors. The distributors subsequently sell them to the consumers. Each member of the POSC will try to optimize its added value. The aim of this paper is to develop an added value formulation as a function of risk, investment and technology levels of each of the POSC member. To facilitate fair distribution of rewards a concept of added value utility based on rsk, investment and technology level was introduced. To optimize the added value distribution between the members the concept of stakeholder dialogue was used. The selling prices were negotiated between the actors until each reached a satisfactory value, which was ruled by the levels of optimum added value utility. This research is important because the developed model can facilitate a better formula to calculate the fair distribution of added values, therefore ensure its sustainability and improve the total supply chain added value.